The potential of zeolite for the remediation of cadmium-contaminated Andisol from Dieng Plateau, Central Java, and its effect on potato vegetative growth - Herliana, Okti; Kharisun, Kharisun; Tamad, Tamad; Sakhidin, Sakhidin (Journal of Degraded and Mining Lands Management, 2026)
Dieng Plateau, with Andisols, is one of the centers for potato cultivation in Indonesia. The intensive use of synthetic chemical fertilizers and pesticides to maximize potato yields has led to high cadmium levels in some potato fields, exceeding the U.S. Environmental Protection Agency's maximum threshold. Cadmium is an immobile heavy metal that can inhibit plant growth and pose health risks. Remediation of the cadmium-contaminated soil is required. This study aimed to elucidate the potential of zeolite for the remediation of cadmium-contaminated soil and the growth of potatoes. The treatments tested in this study were combinations of zeolite doses (5, 10, and 15 t/ha) and particle sizes (50, 100, and 100 mesh) applied to cadmium-contaminated soil. The variables observed were soil properties and potato vegetative growth. The results showed that applying 15 t/ha of 150-mesh zeolite significantly affected soil N, P, K, pH, and, especially, reduced soil Cd concentrations. The application of 10 t/ha of 150-mesh zeolite yielded the greatest increase (73.80%) in potato plant height, number, and leaf area. The application of 15 t/ha of 150-mesh zeolite yielded the lowest cadmium content (0.08 ppm) in the potato plant tissue.